Reviews (New blackfriars, 1966)
THE PERCEPTUAL PROCESS by A. Campbell Garnett THE PHENOMENON OF MAN by Pere Teilhard de Chardin. Fontana, 5s.; THE FAITH OF TEILHARD DE CHARDIN by Henri de Lubac. SJ. Burns Oates. 30s.; TEILHARD DE CHARDIN AND THE MYSTERY OF CHRIST by Christopher Mooney, SJ. Collins, 30s.; GOD'S WORLD IN THE MAKING by Peter Schoonenberg I BELIEVE IN GOD by Yves Moubarac. BIBLE LITURGY AND DOGMA by Yves Moubarac & P. Lucien OCD.THE CHURCH AND CHRISTIAN PRAYER by Hervé Savon. THE CHRISTIAN SOCIAL CONSCIENCE by a group of laymen. ST SEVERIN CATECHISM FOR ADULTS. Geoffrey Chapman LITURGY IN DEVELOPMENT edited by L Alting Von Geusau THE GOD OF OUR FATHERS by Leonard Johnston. 2s FROM ADAM TO ABRAHAM by Joseph Blenkinsopp, 4s. FROM ADVENT TO LENT by Edmund Rood, 4s. THE WORLD MISSION OF THE CHURCH by Adrian Hastings. 2s. THE CHRISTIAN FAMILY IN THE MID-TWENTIETH CENTURY by Noel Timms THE SPIRIT OF THE COMMON LAW, by Richard O'Sullivan THE ADMINISTRATION OF THE DIOCESE OF WORCESTER IN THE FIRST HALF OF THE FOURTEENTH CENTURY by R. M. Haines